Enriched environment alleviates post-stroke cognitive impairment through enhancing α7-nAChR expression in rats - YUAN, Mei; ZHANG, Xin-Xin; FU, Xiao-Cui; BI, Xia (Arquivos de Neuro-Psiquiatria, 2020)
Background: Enriched environment (EE) is a simple and effective intervention to improve cognitive function in post-stroke cognitive impairment (PSCI), partly due to the rebalancing of the cholinergic signaling pathway in the hippocampus. α7-nicotinic acetylcholine receptor (α7-nAChR) is a cholinergic receptor whose activation inhibits inflammation and promotes the recovery of neurological function in PSCI patients. However, it is still unclear whether EE can regulate α7-nAChR and activate the cholinergic anti-inflammatory pathway (CAP) in PSCI. Objective: To investigate the effects of EE on cognitive impairment, and the role of α7-nAChR in PSCI. Methods: A PSCI rat model was induced by middle cerebral artery occlusion and reperfusion (MCAO/R) and were reared in standard environment (SE) or EE for 28d, control group with sham surgery. Cognitive function was determined by Morris water maze test. The long-term potentiation (LTP) was assessed by Electrophysiology. Histopathological methods were used to determine infarct volume, α7-nAChR expression and the cytokines and cholinergic proteins expression. Results: Compared with SE group, rats in EE group had better cognitive function, higher expression of α7-nAChR positive neurons in hippocampal CA1 region. In addition, EE attenuated unfavorable changes induced by MCAO/R in cytokines and cholinergic proteins, and also enhanced LTP promoted by nicotine and attenuated by α-BGT; but showed no significantly difference in infarct volume. Conclusions: EE markedly improves cognitive impairment and enhances neuroplasticity in PSCI rats, which may be closely related to enhancement of α7-nAChR expression.
Keywords: Cognitive Dysfunction; Stroke; Hippocampus